2014
DOI: 10.1007/s40618-013-0032-y
|View full text |Cite
|
Sign up to set email alerts
|

Serum galectin-3 levels in women with PCOS

Abstract: Galectin-3 levels are higher in patients with PCOS, and there is a positive correlation between galectin-3 level and IR, androgen levels and hirsutismus scores. Gal-3 may be a new mediator of PCOS via IR, hyperandrogenism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 33 publications
3
13
3
Order By: Relevance
“…However, these patients were previously known to have diabetes. In a study performed by our group, we reported the correlation of galectin-3 levels with insulin resistance in patients with polycystic ovary syndrome [16]. Until now, the effect of Gal-3 on the development of prediabetes and T2DM has remained unclear.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, these patients were previously known to have diabetes. In a study performed by our group, we reported the correlation of galectin-3 levels with insulin resistance in patients with polycystic ovary syndrome [16]. Until now, the effect of Gal-3 on the development of prediabetes and T2DM has remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired glucose tolerance (IGT) is defined as 2hPG values in the 75-g OGTT of 140 to 199 mg/dL [14]. IFG, IGT, or both of these conditions are accepted as prediabetes [16]. We used the following two criteria for the diagnosis of diabetes: FPG ≥126 mg/dL and 2hPG ≥200 mg/dL [16].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Galectin‐3 is a member of soluble β‐galactoside‐binding lectin, which plays an important role in the development of inflammation and fibrosis . Previous studies have shown that increased galectin‐3 expression was observed in various cancer cells .…”
Section: Introductionmentioning
confidence: 99%